Zinc oxide, lidocaine, hot water, and lateral internal sphincterotomy for fissure-in-ano: Randomized controlled study (Annals of Medical Research, 2021)
None
Keywords: Zinc Oxide; Chronic Anal Fissures; Medical Treatment.